PERILAKU SUAMI TENTANG PENTINGNYA PERAN SUAMI SIAGA DALAM MASA KEHAMILAN DI DESA HUTALOMBANG KECAMATAN LUBUK BARUMUN KABUPATEN PADANG LAWAS TAHUN 2018 - KUMALA SARI RAMBE (JURNAL ILMIAH MAKSITEK, 2019)
Based on WHO research, in the world in 2007 coverage of Antenatal Care was found in pregnant women (76.4%). Nationally, performance indicators for coverage of K4 pregnant women health services in 2014 amounted to 86.70%, not achieving the Strategic Plan target (Renstra). Ministry of Health in the same year, which is 95%. there are three provinces that have coverage of K4 pregnant women with less than 50%, namely West Papua (39.74%), Maluku (47.87%), and Papua (49.67%). The purpose of this study was to determine the Husband's Behavior About the Importance of the Role of a Prepared Husband in Pregnancy in Hutalombang Village. This research method is descriptive, using primary and secondary data conducted by distributing questionnaires to 53 respondents, taking samples using Accidental Sampling. The results were obtained based on the knowledge of the majority of respondents with sufficient knowledge of 34 respondents (64.1%), and a minority of respondents with less knowledge of 5 respondents (9.4%). Based on the attitude of the majority being positive as many as 47 respondents (88.7%), and the majority being negative as many as 6 respondents (11.3%). Based on the action, the majority of actions were carried out by 30 respondents (56.6%), and the majority of actions were not as many as 23 respondents (43.4%). From the above data it can be concluded that the husband's knowledge, attitudes and actions regarding the importance of the husband's role during pregnancy in Hutalombang Village are in the sufficient category. It is hoped that the husband will be more active in increasing his knowledge, attitudes, and actions, especially regarding the role of the standby husband.